Identification of HLA‐B*14:41N in a NMDP Hispanic donor, selected for a patient of The Unrelated Mexican Donor Registry‐DONORMO program in Mexico. Issue 3 (20th July 2015) - Alaez, C.; Flores‐A, H.; Munguía, A.; Gorodezky, C.
<x xml:space="preserve">Abstract</x> The B*14:41N allele was identified in a The National Marrow Donor Program (NMDP) Hispanic donor typed by our Mexican Registry‐DONORMO